Impact of glucocorticoids on short-term and long-term outcomes in patients with relapsed/refractory multiple myeloma treated with CAR-T therapy - Wang, Xue; Qi, Yuekun; Li, Hujun; Liu, Fengan; Cao, Jiang; Chen, Wei; Wang, Ying; Qi, Kunming; Yan, Zhiling; Zhu, Feng; Li, Zhenyu; Cheng, Hai; et al. (Frontiers in Immunology, 2022)
Background Glucocorticoids (GCs) are often used to treat cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS). The effects of GCs on the efficacy of CAR-T cell treatment in relapsed/refractory multiple myeloma (RRMM) have not been fully established. We evaluated the impact of GCs on clinical outcomes of RRMM patients treated with CAR-T cells. Methods This study involved RRMM patients treated with CAR-T cells at our center between June 2017 and December 2020. Patients were stratified into GC-used group (GC-group) and non-GC-used group (NGC-group). CRS or ICANS was graded on the basis of the American Society of Transplantation and Cellular Therapy consensus grading system. Response status was evaluated by the IMWG Uniform Response Criteria. The duration of response (DOR), progression-free survival (PFS), and overall survival (OS) were calculated. Result A total of 71 patients were included in this study. In the NGC group (40 patients), 34 (85%) had responses to CAR-T cell therapy, including 16 (40%) stringent complete response (sCR), seven (17.5%) complete response (CR), five (12.5%) very good partial response (VGPR), and six (15%) partial response (PR). The overall response rate (ORR) and complete response rate (CRR) in the NGC group were 85% and 57.5%. In the GC group (31 patients), 29 (93.5%) had responses, including 11 (35.5%) sCR, nine (29%) CR, two (6.4%) VGPR, and seven (22.6%) PR. Differences in ORR and CRR between the two groups were insignificant. The dose, duration, and timing of GCs did not affect ORR and CRR. At a median follow-up of 28.2 months, the median PFS was 20.4 months (95% CI, 7.9 to 32.9) while the median OS was 36.6 months (95% CI, 25.9 to 47.2) for the GC group. The median PFS and OS for the NGC group were 13.7 months (95% CI, 8.8 to 18.6) and 27.5 months (95% CI, 14.1 to 41.0). There were no significant differences in either PFS or OS between the GC group and the NGC group. Differences in median DOR for the patients with CR or better in the GC group and NGC group were not significant (p = 0.17). Earlier, prolonged use and high dose of GCs were not associated with any effects on either PFS or OS. Additionally, GCs had no effects on CAR-T cell proliferation. Conclusion Administration of GCs, dose, timing, and duration does not influence the clinical efficacy of CAR-T cells in RRMM in this study.